Knowledge and practices of Dentists who prescribe in specialized centers of the public health system: a cross-sectional study (Research, Society and Development, 2021)
The aim of this study was to analyze the profile of prescribing dentists, the factors that influence prescriptions and the most frequently prescribed medications in Dental Specialty Centers. A cross-sectional study was carried out, where dentists working in specialty centers answered a structured questionnaire, anonymously. The questionnaire consisted of demographic data, levels of professional training, sources of knowledge and information on the subject, frequency of prescription and indication of the most prescribed drugs. Thirty-four professionals (73.9%) agreed to participate in the study. Scientific articles, participation in scientific events and contact with other professionals represent the main source of information reported by prescribers. Paracetamol (60.4%) was the most prescribed drug for mild pain and ibuprofen (71.4%) to control severe pain. Amoxicillin (55.2%) was the most prescribed antimicrobial by dentists. The overall average of correct answers, associated with categorized data, was 68%. Positive correlations were found between time since graduation and the concept of rational use of medications. While, for knowledge about antimicrobial prophylaxis, a negative correlation was identified. There was no statistical difference between the mean scores of professionals trained in public and private institutions, as well as for the levels of professional training. The academic and continuing education of the prescriber is crucial for the rational prescription of drugs in Dentistry.